Four new degradation products of doxorubicin: An application of forced degradation study and hyphenated chromatographic techniques - Dheeraj Kaushik; Gulshan Bansal (Elsevier, 2015)
Forced degradation study on doxorubicin (DOX) was carried out under hydrolytic condition in acidic, alkaline and neutral media at varied temperatures, as well as under peroxide, thermal and photolytic conditions in accordance with International Conference on Harmonization (ICH) guidelines Q1(R2). It was found extremely unstable to alkaline hydrolysis even at room temperature, unstable to acid hydrolysis at 80Â Â°C, and to oxidation at room temperature. It degraded to four products (O-IâO-IV) in oxidative condition, and to single product (A-I) in acid hydrolytic condition. These products were resolved on a C8 (150Â mmÃ4.6Â mm, 5Â Âµm) column with isocratic elution using mobile phase consisting of HCOONH4 (10Â mM, pH 2.5), acetonitrile and methanol (65:15:20, v/v/v). Liquid chromatographyâphotodiode array (LCâPDA) technique was used to ascertain the purity of the products noted in LCâUV chromatogram. For their characterization, a six stage mass fragmentation (MS6) pattern of DOX was outlined through mass spectral studies in positive mode of electrospray ionization (+ESI) as well as through accurate mass spectral data of DOX and the products generated through liquid chromatographyâtime of flight mass spectrometry (LCâMSâTOF) on degraded drug solutions. Based on it, O-IâO-IV were characterized as 3-hydroxy-9-desacetyldoxorubicin-9-hydroperoxide, 1-hydroxy-9-desacetyldoxorubicin-9-hydroperoxide, 9-desacetyldoxorubicin-9-hydroperoxide and 9-desacetyldoxorubicin, respectively, whereas A-I was characterized as deglucosaminyl doxorubicin. While A-I was found to be a pharmacopoeial impurity, all oxidative products were found to be new degradation impurities. The mechanisms and pathways of degradation of doxorubicin were outlined and discussed. Keywords: Doxorubicin, TOF, Forced degradation, Liquid chromatography, Degradation product, Mass fragmentation pattern